2022
DOI: 10.1159/000523905
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibits Glioblastoma Growth and Prolongs Survival Rate through Inhibiting Glycolytic Metabolism

Abstract: Introduction: Quercetin has been reported to have anti-tumor activity of a wide range of cancers, including breast, lung, colon, prostate. Here, we investigated the protective role of quercetin in glioblastoma (GBM), which causes higher risk of morbidity and mortality, and explored the anti-tumor effects of quercetin on GBM using the U87MG and T98G cells and GBM mouse models. Methods: Cell viability and colony formation assays were performed by CCK-8 and clone formation assays. GBM xenograft mouse model was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Plant-derived quercetin is a favonoid with anticancer and antiproliferative properties [24]. According to multiple lines of evidence [25,26], a variety of proteins involved in GBM cell signaling are regulated by quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived quercetin is a favonoid with anticancer and antiproliferative properties [24]. According to multiple lines of evidence [25,26], a variety of proteins involved in GBM cell signaling are regulated by quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the failure of GBM therapy is that the BBB restricts the distribution of drugs in the brain. In recent years, many active ingredients of traditional Chinese medicine have made significant breakthroughs in the direction of anti-GBM, which achieved through various biological mechanisms to inhibit the occurrence of glioma ( Shi et al, 2022 ; Wang et al, 2022 ). We obtained irigenin by screening on the TCMSP database ( https://old.tcmsp-e.com/tcmsp.php ), from which BBB value showed that it could penetrate the blood-brain barrier ( Tattersall et al, 1975 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have shown that this compound has antioxidant, 5 anti-inflammatory 6 and anti-cancer properties. 7 This antitumor activity can be exerted via several mechanisms such as alteration of tumour metabolism, 8 inhibition of angiogenesis, 9 improvement of tumours' chemosensitivity, 10 inhibition of the epithelial-tomesenchymal transition, 11 decreasing tumour invasion potential through downregulation of matrix metalloproteinases, 12 induction of apoptosis and inhibition of anti-apoptotic pathways. 13,14 Despite its efficacy and minimal side effects, the clinical application of quercetin is limited due to its low bioavailability.…”
mentioning
confidence: 99%